A comparison of propofol and etomidate as anaesthetic agents for elective non-cardiac surgery - Kumar, Amit; Shekhawat, Kamlesh Kanwar; Sharma, Roma; Mangwana, Pramod (International Journal of Research in Medical Sciences, 2018)
Background: To compare propofol and etomidate as anaesthetic agents for elective non-cardiac surgery with respect to stability of haemodynamic parameters, systemic side effects and quality of induction. Methods: Randomised, blinded study of 100 patients posted for elective non-cardia surgery under general anaesthesia, divided in to two group. In group P(n=50) induction was achieved with injection Propofol 1mg/kg, whereas in group E(n=50), it was achieved with injection etomidate 0.3mg/kg after premedication with injection midazolam 0.04mg/kg and fentanyl 2µg/kg in both the group. Hemodynamic parameters like, heart rate, systolic BP, diastolic BP, Mean BP and induction time in seconds, pain on injection, myoclonus, post-operative nausea, vomiting were recorded at different time intervals (base line, at induction, immediately after intubation and 1,3,5 and 15 min after intubation). Results: There was no statistically difference was found in demographic profile and baseline hemodynamic parameters but significant different was found in intraoperative mean HR, SBP, DBP, MBP at various time intervals, and our result was more in favour of E group as compare to P, in which above recorded vital parameters were decreased more than E and induction time was also faster in E as compare to P. Pain on injection and post-operative nausea, vomiting was more in group P as compare to E, however the myoclonus movements was more in E group as compare to P but statistically not significant. Conclusions: Etomidate is a better intravenous induction agent of anaesthesia than Propofol in hemodynamically unstable patient also as it has faster onset of action with less pain and post-operative nausea, vomiting with good hemodynamic stability.